2006
DOI: 10.1071/wf05090
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial characteristics of forest fires in South Korea between 1970 and 2003

Abstract: Information on the temporal and spatial patterns of forest fires can contribute to efficient forest fire management. To evaluate the readjustment of forest fire precautionary periods and to provide information for forest fire prevention and suppression strategies, the temporal and spatial characteristics of forest fire occurrences and spread in Korea were analysed using statistics from 1970 to 2003. Monthly forest fire occurrences and burned area were examined using time-series analysis, and F-tests were condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…A better knowledge on spatial patterns of fire occurrence and their relationships with underlying factors of human risk becomes a necessity to locate and make prevention efforts more efficient. Given the time spans required for prevention planning, databases encompassing several years are usually called for when considering wildfire occurrence trends (the 1983-2001 time period in the study by De la Riva et al, 2004;1981in Genton et al, 20061989-1996in Preisler et al, 20041970 in Lee et al, 2006;-2002 in Maingi and Henry, 2007;1976in Schoenberg et al, 2007in Sturtevand and Cleland, 20071970 time period in the study by Vasilakos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A better knowledge on spatial patterns of fire occurrence and their relationships with underlying factors of human risk becomes a necessity to locate and make prevention efforts more efficient. Given the time spans required for prevention planning, databases encompassing several years are usually called for when considering wildfire occurrence trends (the 1983-2001 time period in the study by De la Riva et al, 2004;1981in Genton et al, 20061989-1996in Preisler et al, 20041970 in Lee et al, 2006;-2002 in Maingi and Henry, 2007;1976in Schoenberg et al, 2007in Sturtevand and Cleland, 20071970 time period in the study by Vasilakos et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Historical fire inventories of burned area and fire frequency are commonly used for monitoring wildfire properties. For example, time series of historical burned area at different time scales [Riaňo et al, 2007;Pereira et al, 2011] have been used to quantify the fire season length and the timing of the start of the fire season [Taylor and Skinner, 2003;Lee et al, 2006;Westerling et al, 2006], and the reported time between the first wildfire discovery date and the last wildfire control date has been applied to derive the long-term variation in the fire season [Westerling et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…En el ámbito de los incendios forestales, la cartografía del número, localización y área afectada resulta especialmente útil de cara a disponer de información suficiente para realizar un análisis apropiado de la distribución espacial de este fenómeno (Arino et al, 2001). Este tipo de análisis permite extraer conclusiones acerca del grado de actividad de cada una de las variables que en él intervienen, además de mostrar la sensibilidad al fuego que presentan las diferentes regiones (Lee et al, 2006;Verdú, 2007). En este aspecto, la teledetección constituye una inestimable fuente de información de cara a la prevención (localización de medios en áreas de fuerte incidencia histórica, validación de modelos de riesgo, etc.)…”
Section: Introductionunclassified